Desordens osteomusculares em alunos de odontologia - Santos, Renata Reis dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Painful symptoms in musculoskeletal system is a major concern among Dentists. However, only recently there is a scientific evidence to suggest a relationship between the tasks and musculoskeletal symptoms. In addition, dental students perform the same clinical tasks that a Dentist who works in the clinic. The objective of this research was to evaluate the prevalence of painful symptoms and associated factors; and the perception of dental students in relation to the risk factors that may contribute to the occurrence of musculoskeletal symptoms and also to determine the existence of painful symptoms influence the perception of factors. A cross-sectional study, each student responded to three self-administered questionnaires was conducted. The first consists of sociodemographic variables; about his academic life; harmful habits; physical activity and the General Health. Although we collected information on weight and height, to be subsequently performed calculating the Body Mass Index (BMI). The second instrument used was the Nordic Musculoskeletal Questionnaire, which evaluated the musculoskeletal disorders. The relationship between pain symptoms and the other variables studied, it was considered as positive painful symptomatology was reported at least one yes response in any area of the body. The third questionnaire used was the Instrument on work factors that can contribute to musculoskeletal symptoms. To analyze the perception of risk factors the students were divided into two groups (with and without pain). It was done association test groups with the categories of risk perception instrument and comparison between means using the Mann-Whitney and t test. The presence of pain in the last 12 months was observed in 199 participants (82.6%). There was association between pain symptoms in the last 12 months in at least...

A sintomatologia dolorosa no sistema músculo-esquelético é uma grande preocupação entre os cirurgiões-dentistas. Os estudantes de Odontologia realizam as mesmas tarefas clínicas que um cirurgião-dentista que já atua na clínica, mas apenas recentemente se tem evidências científicas que sugerem uma relação entre as tarefas e os sintomas músculo-esqueléticos. Os objetivos desta pesquisa foram; avaliar a prevalência de sintomatologia dolorosa e fatores associados; além da percepção dos acadêmicos de Odontologia em relação aos fatores de riscos que podem contribuir no aparecimento de sintomas osteomusculares, bem como verificar se a existência de sintomatologia dolorosa influencia na percepção dos fatores. Foi realizado um estudo transversal, com 241 alunos matriculados em disciplinas clínicas do curso de Odontologia, em que cada um respondeu a três questionários autoaplicáveis. O primeiro foi composto por variáveis sociodemográficas; sobre sua vida acadêmica, hábitos nocivos, atividades físicas e saúde geral. Ainda foram coletadas informações sobre o peso e altura, para que fosse realizado posteriormente o cálculo do Índice de Massa Corporal (IMC). O segundo instrumento utilizado foi o Questionário Nórdico de Sintomas Osteomusculares, que avaliou as desordens osteomusculares. Para verificar a associação entre a sintomatologia dolorosa e as outras variáveis estudadas, considerou-se como sintomatologia dolorosa positiva quando se relatou pelo menos uma resposta afirmativa em alguma área do corpo. O terceiro questionário utilizado foi o Instrumento sobre fatores do trabalho que podem contribuir para sintomas osteomusculares. Para a análise da percepção dos fatores de riscos, os alunos foram divididos em dois grupos (com e sem dor). Realizou- se o teste de associação dos grupos...
Keywords: Odontologia; Dor musculoesquelética; Estudantes de odontologia; Saúde do trabalhador; Dentistry